2012
DOI: 10.1152/ajprenal.00470.2011
|View full text |Cite
|
Sign up to set email alerts
|

HSP47 regulates ECM accumulation in renal proximal tubular cells induced by TGF-β1through ERK1/2 and JNK MAPK pathways

Abstract: Heat shock protein (HSP)47 is a collagen-specific molecular chaperone that is essential for the biosynthesis of collagen molecules. It is likely that increased levels of HSP47 contribute to the assembly of procollagen and thereby cause an excessive accumulation of collagens in disease processes associated with fibrosis. Although HSP47 promotes renal fibrosis, the underlying mechanism and associated signaling events have not been clearly delineated. We examined the role of HSP47 in renal fibrosis using a rat un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…HSP47 may be involved in the initial stage of fibrosis via the TGF-β1induced transdifferentiation of fibroblasts to myofibroblasts, as well as at the later stage of fibrosis, the collagen synthesis in already transdifferentiated myofibroblasts (Hong et al 2012). HSP47 increases the expression of collagen type I, collagen type IV, fibronectin, and tissue-type plasminogen activator inhibitor in human proximal tubular epithelial (HK-2) cells, suggesting the functionality of HSP47 in regulating ECM synthesis and degradation in processes related to renal tubulointerstitial fibrosis (Xiao et al 2012).…”
Section: Hsp47mentioning
confidence: 99%
“…HSP47 may be involved in the initial stage of fibrosis via the TGF-β1induced transdifferentiation of fibroblasts to myofibroblasts, as well as at the later stage of fibrosis, the collagen synthesis in already transdifferentiated myofibroblasts (Hong et al 2012). HSP47 increases the expression of collagen type I, collagen type IV, fibronectin, and tissue-type plasminogen activator inhibitor in human proximal tubular epithelial (HK-2) cells, suggesting the functionality of HSP47 in regulating ECM synthesis and degradation in processes related to renal tubulointerstitial fibrosis (Xiao et al 2012).…”
Section: Hsp47mentioning
confidence: 99%
“…RIF is caused by the loss of normal renal units, the proliferation of fibroblasts and myofibroblasts, and the production and accumulation of extracellular matrix [2]. Recent studies have indicated that the progression of RIF involves various molecular signaling pathways, such as TGF-β/Smad [3], p38 MAPK [4], extracellular signal regulated kinase 1/2, and cJun N-terminal kinase [5]. For decades, considerable efforts have been devoted to studying the pathogenesis of RIF, but its molecular mechanism remains unresolved to date [6].…”
Section: Introductionmentioning
confidence: 99%
“…8), consistent with the findings from our network prediction. Indeed, some other HSPs, such as HSP47, HSP70, and HSP90, but not HSP60, have been reported to play important roles in ECM protein regulation (4749). These data indicate that HSP60 may have no significant role in ECM homeostasis (as shown in our study, fibronectin).…”
Section: Resultsmentioning
confidence: 99%